Putting the United States in North America - Richard John (Centre de Recherches sur les Mondes Américains, 2010)
This essay surveys the transnational social processes that shaped the United States in the period between the American War of Independence (1775-1781) and the entry of the United States in the First World War in 1917. The focus is on territorial expansion and economic development. Contrary to a common assumption in the historiography, it contends that, during this period, the United States was linked not only to the Europe, but also to North America, and, in particular, to Canada and Mexico. Building on this “continentalist” perspective, the essay raises questions about the concept “American”; the expansionist impulse that is often called the “conquest of the West”; and the so-called “weakness” of the nineteenth-century U. S. state. Each of these constructs shifts its meaning if the United States is compared with its neighbors to the north and south, rather than to the nation-states of Europe.